2019
DOI: 10.1002/prp2.536
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of oral hypoglycemic agents in Japanese patients with type 2 diabetes mellitus and risk of depression: A retrospective cohort study

Abstract: Type 2 diabetes mellitus (T2DM) is a risk factor for depression. Since brain insulin resistance plays a potential role in depression, the future risk of depression in patients with T2DM may be altered depending on the class of oral hypoglycemic agent (OHA) used for T2DM therapy. The aim of the present study was to determine if specific classes of OHAs are associated with a risk for comorbid depression in T2DM. Japanese adult patients with T2DM (n = 40 214) were divided into a case group (with depression; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Different classes of hypoglycemic agents have different effects on the risk of depression in patients with T2DM. The results of a retrospective cohort study of 40,214 adult patients with T2DM who were not treated or treated with single or combined oral hypoglycemic agents where depression was used as an outcome measure ( 32 ) showed that dipeptidyl peptidase 4 (DPP-4) inhibitors and SGLT-2 inhibitors were both significantly associated with a reduced risk of depression, while biguanides, sulfonylureas, α-glucosidase inhibitors, thiazolidinediones, and glinides did not show to be associated with a reduced risk of depression. Because only one patient in the study was treated with SGLT-2 inhibitors, and the study was a non-randomized retrospective study with many confounding factors, the conclusions must be further verified.…”
Section: Treatmentmentioning
confidence: 99%
“…Different classes of hypoglycemic agents have different effects on the risk of depression in patients with T2DM. The results of a retrospective cohort study of 40,214 adult patients with T2DM who were not treated or treated with single or combined oral hypoglycemic agents where depression was used as an outcome measure ( 32 ) showed that dipeptidyl peptidase 4 (DPP-4) inhibitors and SGLT-2 inhibitors were both significantly associated with a reduced risk of depression, while biguanides, sulfonylureas, α-glucosidase inhibitors, thiazolidinediones, and glinides did not show to be associated with a reduced risk of depression. Because only one patient in the study was treated with SGLT-2 inhibitors, and the study was a non-randomized retrospective study with many confounding factors, the conclusions must be further verified.…”
Section: Treatmentmentioning
confidence: 99%
“…The main reason for a poor rating was lack of adjustments for sex, age, BMI or antidepressant medication use, or not adjusting for baseline values or disease status of the relevant dependent variable. Three studies used a selective study population such as only including men, 24 mainly including women with microalbuminuria, 45 or individuals with a longer disease duration and a low prevalence of probable depression in the study sample, 47…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Regarding depression, increased DPP-4 activity has been shown to positively correlate with Patient Health Questionnaire-9 (PHQ-9) scores and depression severity in T2D patients (Zheng et al, 2017). A retrospective cohort study in a large group of patients with T2D showed that chronic (minimum of 30 days) use of DPP-4 inhibitors might reduce the risk of depression (Akimoto et al, 2019). These drugs, responsible for inhibiting GLP-1 degradation, are thought to indirectly increase neuronal receptors' activation for this peptide (GLP-1R), which can easily cross the blood-brain barrier (Hunter and Hölscher, 2012).…”
Section: Incretin Drugsmentioning
confidence: 99%